Charge and exciton dynamics of OLEDs under high voltage nanosecond pulse: towards injection lasing - Viqar Ahmad (Nature Portfolio, 2020)
Though efforts toward electrically-pumped lasers based on simple organic light-emitting diode (OLED) structures have been reported, a comprehensive model is needed to elucidate key optoelectronic processes. Here, the authors report a model describing OLED operation under high current densities.